Organic geochemistry of Ordovician ultra-deep natural gas in the north Shuntuoguole area, Tarim Basin, NW China: Insights into genetic types, maturity, and sources - Jia, Zhenjie; Hou, Dujie; Zhu, Xiuxiang; Bian, Jiejing; Ma, Xiaoxiao (Frontiers in Earth Science, 2023)
As a gas-rich region in the Tarim Basin, the northern Shuntuoguole area (also known as the Shunbei area) is an attractive prospect. Nonetheless, the debate about the origins of these natural gas continues. The analysis on the geological context, natural gas components, and the carbon and hydrogen isotope ratios prove that methane is the predominate component of alkane gases. The Shunbei area has stable carbon isotope compositions of methane (δ13C1), ethane (δ13C2), and propane (δ13C3) that vary from −51.7‰ to −44.2‰, −39.3‰ to −28.6‰, −35.6‰ to −25.4‰, respectively. Alkane gases' carbon isotope fractionation (δ13C2 < −28 ‰ and δ13C3 < −25‰) shows that they are oil-associated gas, and their parent material type is I kerogen. Natural gas can be broken down further into three subgroups—Type I1, Type I2, and Type I3—based on the link between the carbon number 1/n and δ13Cn of the gas. Type I1 gas has relatively enriched δ13C, with δ13C1 and δ13C2 of −47.5‰ to −44.2‰ (−45.85‰ on average) and −28.6‰ to −29.9‰ (−29.3‰ on average), respectively. Compared to Type I1 gas, however, Type I2 and Type I3 gas have significantly lower levels of δ13C. Modified plots of lnC1/C2 vs. lnC2/C3 reveal that kerogen cracking is the primary source of natural gas in the Shunbei area, and that this gas is combined with the contribution of oil cracking gas. Petroleum exploration and development in the Shunbei area can be justified on the basis that natural gas in the area originate primarily from Ordovician source rocks, as shown by carbon isotopic compositions.